Teaching Efficacy in Inclusive Education (IE) in Indonesia and other Asia, Developing Countries: a Systematic Review - Ika Febrian Kristiana; Wiwin Hendriani (Intelektual Pustaka Media Utama, 2018)
Inclusive education involving disable students has been applied in several countries including Asian countries. Nevertheless, teachers’ efficacy in implementing inclusive education remains out of sight. This review aims to summarize some facts depicting teachers’ efficacy in an inclusive education (IE) setting taking place in several Asian countries, particularly in developing countries. The search of e-literature was conducted to identify full-English articles published since 2004 concerning on teachers’ efficacy in teaching in inclusive programs/schools. The database used in searching the appropriate literatures was the database assembled in August 2017 which contained social-science articles such as PsycARTICLES, ERIC, Sciencedirect, SSCI, Springer Link, and Google Scholar. There were two studies identified using inclusive and exclusion criteria stipulation in this review. Teachers’ teaching efficacy in inclusive education (IE) in Indonesia and Bangladesh as developing countries in Asia – including efficacy in use inclusive instruction, efficacy in managing behavior, and efficacy in collaboration – was categorized in a good condition. Improving the measurement and research on teachers’ efficacy in teaching in an inclusive program/school will require greater investment in arranging several inclusive teachers’ professionalism enhancement and the increase in the number of disable students acquiring their education rights